Extended‐release naltrexone for methamphetamine dependence among men who have sex with men: a randomized placebo‐controlled trial. (29th August 2017) - Coffin, Phillip O.; Santos, Glenn‐Milo; Hern, Jaclyn; Vittinghoff, Eric; Santos, Deirdre; Matheson, Tim; Colfax, Grant; Batki, Steven L.
Abstract: Background and aims: Methamphetamine use is increasingly prevalent and associated with HIV transmission. Early‐phase human studies suggested naltrexone reduced amphetamine use among dependent individuals. We tested if extended‐release naltrexone (XRNTX) reduces methamphetamine use and associated sexual risk behaviors among high‐risk methamphetamine‐dependent men who have sex with men (MSM). Design: Double‐blind, placebo‐controlled, randomized trial of XRTNX versus placebo over 12 weeks from 2012 to 2015. Setting: San Francisco Department of Public Health, California, USA. Participants: One hundred community‐recruited, sexually‐active, actively‐using methamphetamine‐dependent MSM. Mean age was 43.2 years; 96% were male, 3% transfemale, and 1% transmale; 55.0% were white, 19.0% African American, and 18.0% Latino. Interventions: XRNTX 380 mg ( n  = 50) or matched placebo ( n  = 50) administered by gluteal injection at 4‐week intervals. Measurements: Regression estimated average level and change in level of positive urines during the period 2–12 weeks (primary outcomes) and sexual risk behaviors (secondary outcome). Findings: Ninety per cent of visits were completed. By intent‐to‐treat, participants assigned to XRNTX had similar differences during 2–12 weeks in methamphetamine‐positive urines as participants assigned to placebo [incidence rate ratio (IRR) = 0.95, 95% confidence interval (CI) = 0.76–1.20; Bayes factor < 0.3]. Observed urine positivity declined from 78 to 70% in the XRNTX arm and 74 to 64% in the placebo arm. Adherence to injections was 96.7% in the XRNTX arm and 91.3% in the placebo arm. Sexual risk behaviors declined similarly among participants in both arms (all P  > 0.05). There were no serious adverse events related to study drug and no differences in frequency of adverse events by treatment arm. Conclusions: Notwithstanding very high medication adherence for this study, extended‐release naltrexone does not appear to reduce methamphetamine use or sexual risk behaviors among methamphetamine‐dependent men who have sex with men compared with placebo.